The aesthetic tendencies of early modernity in South-East Asia: the hybrid language of aristocratic palaces of the early 1900s in Malaysia - Jahn Kassim, Puteri Shireen; Mohd Nawawi, Norwina; Abdul Majid, Noor Hanita; Raja Abdul Kadir, Tengku Anis Qarihah; Abdullah, Alias (UMK Press, 2018)
South-East Asian ‘Nusantara’ architecture , in the post-colonial era, is characterized by a historical cleavage between a ‘modern’ present and a ‘traditional’ past. The paper attempts to bridge this rupture through mapping early modernist stylistic tendencies in Malay palaces and characterizing their development through an evolvement of modernizing strands in their hybrid language. In Malaysia, a rupture between a traditional ‘pre –modern’ era and the post-independence period can be bridged by tracing the stylistic evolution which are observed in hybrid cases of palatial design, seen as the public monuments of its time. This evolution representing episodes of early ‘modernity’ s as observed during the late 1800s and early 1900s. They represent tendencies that are pulled into two different directions of modernity – one end by imported styles – and the other, by local traditions rooted in the Malay culture and polity. Irrevocable changes was spurred from the 1800s onwards due to the pressure of external forces, which consequently brought to the final phase of the evolution of the local endemic (Malay) style before a total stylistic change in the aesthetic style of public buildings had overcome the traditional language and type forms.